Getting over the Crisis of Identity for Stabilization of the Personality Professional Health - Ivanova, N. L. (Psychological Prospects Journal, 2012)
This article is devoted to the development of the psychologist’s professional health. We consider professional health as an important part of the psychological health in general. Successful getting over the professional crisis of identity ensures professional health. Professional identity occupies especial place in the structure of personality. Professional identity is a whole formation consisting of cognitive, motivational and valuable characteristics. It is not stable in the process of education. Students-graduators have more implications of identity crisis. In order to get over the crisis a person should get skills: 1) to reflect the changes in the social environment, 2) to develop own value system, 3) to analyze own professional identity.